THERAPEUTIC MANAGEMENT OF HYPERTENSION AND HYPERLIPIDEMIA IN TYPE-2 DIABETES MELLITUS PATIENTS IN SOUTHWESTERN REGION OF SAUDI ARABIA: A PHARMACIST PERSPECTIVE - Khan, Noohu Abdulla; VV, VENKATACHALAM; AL-AKHALI, KHALED M; ALAVUDEEN, SIRAJUDEEN S; CK, DHANAPAL; ANSARI, SHAIK MOHAMMAD ASIF (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The main objective of this study was to evaluate the therapeutic management of hypertension (HTN) and hyperlipidemia in Type 2 diabetes mellitus (T2DM) patients in Aseer Diabetic Center, southwestern region of Saudi Arabia. Methods: This is a cross-sectional retrospective study in adult T2DM patients. A total number of 343 patient's records was randomly selected from the patient medical records section. Among the 343 T2DM patients, all were hyperlipidemics, and only 228 patients were Hypertensive. The collected raw data were recorded and statistically analyzed with Windows Microsoft Excel 2007. Descriptive statistics of mean, standard deviation, and frequencies were performed on the sample, one-way ANOVA was used to analyze the continuous data by using Graphpad software version-5; p≤0.05 was considered statistically significant. Result: The systolic blood pressure (BP) was found to have statistically significant difference (p≤0.0320) after treatment, but there is no statistical difference in diastolic BP. Glycemic control was found to have statistically significant difference (p≤0.0039). Most of the patients were treated with captopril -25 mg (angiotensin-converting enzyme inhibitor class drug). All the lipid profile high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total cholesterol showed statistically significant difference after treatment except triglycerides. Most of the patients were prescribed with statins for hyperlipidemia. Conclusion: In this study, systolic HTN is better controlled with statistically significant difference compared to diastolic HTN. In the current study, lipid control was better than glycemic control. Updating of the drug formulary to have new therapeutic agents can improve the current status. Keywords: Hyperlipidemia, Hypertension, Saudi Arabia Southwestern region, Therapeutic management, Type 2 diabetes.